DEVELOPING INTERACTIVE TEACHING MATERIAL FOR RAMADHAN GLOSSARY IN JUNIOR HIGH SCHOOL STUDENTS - Shofiyatul Fikriyani; Respatyastu PranaJati Dt; Nilwanto; M. Syukron Katsir; Fitriatul Hidayah; Fardini Sabilah (University of Muhammadiyah Malang, 2022)
The focus of this research is to determine 8th-grade junior high school students and teachers’ learning and teaching perspectives about English and their learning and teaching needs for short functional text (SFT) for developing interactive video for Ramadan Glossary. Utilizing the initial step of Borg and Gall research development processes, this study was carried out a junior high school in Malang – East Java province and two junior high schools in Riau islands Sumatera. A total of 60 students and five English teachers participated in this research and voluntarily filled up questionnaires to meet the objectives of this study. The findings revealed that all students and teachers believed that SFT should be presented interactively. They suggested that interactive was suitable to be developed to meet the students and teachers’ needs of teaching materials about Ramadan Glossary which were divided into three groups: Ramadan Preparation, During Ramadan, and After Iftar. The interactive video is suggested due to its potential to enhance students’ engagement in learning English skills using SFT. Therefore, the findings of this research provide valuable insights into effective English teaching practices.